Ex vivo quantitative amyloid and perivascular space measurements in white and gray matter on immunohistological microscopy in AD, MCI, and cognitively intact individuals. (20th December 2022) - Schwartz, Daniel L; Roese, Natalie E; Hurworth, Justin; Lahna, David; Krajbich, Victoria; Kaye, Jeffrey A; Dodge, Hiroko H; Woltjer, Randy; Silbert, Lisa C
Abstract: Background: Amyloid (Aβ) clearance is disturbed in late‐onset Alzheimer's disease (AD), and a local relationship between Aβ clearance and gray (GM) and white matter (WM) perivascular spaces (PVS) is presumed. Most in vivo primate work has focused on MRI‐visible PVS in WM, described as pathological and enlarged, while nearly all in vivo mechanistic work in animals interrogates "normal" GM PVS. This disparity describes a critical knowledge gap in the morphology, location and relevance of PVS to Aβ clearance. Method : Ex vivo samples from four locations in 22 NIA‐Layton Oregon Alzheimer's Disease Research Center participants (mean age at death=92y). Pre mortem diagnoses were cognitively intact ("C", N=9), mild cognitive impairment ("MCI", N=5), and AD (N=8, confirmed post mortem ). Samples were sliced, stained and digitized (3.52µm/pixel). GM masks and morphometrics of vessels>6200µm 2 in WM (n=1403) and GM (n=237) were derived from trichrome stain (Fig. 2H, C, and D). Aβ coverage (% positive 4G8 pixels in GM pixels within 1.76mm of the nearest GM pixel to the vessel center‐of‐mass) and normalized PVS size were used as dependent variables (Fig. 2D&F). Result: There were significant main effects of group for Aβ burden in GM nearest to WM vessels (C<MCI<AD). Main group effects for Aβ around GM vessels were ordered differently (C>AD>MCI) (Fig. 3D). There were significant main effects of group for PVS size in GM (AD>MCI and C) but not WM (Fig. 3C). There were no vessel‐by‐vessel associations between PVSnorm and nearby cortical amyloid within group. (Fig. 3E) Conclusion: In MCI, relatively smaller PVS and high cortical Aβ near GM vessels may reflect a functional waste clearance system in those for whom Aβ burden is not yet advanced. In AD, large GM PVS and an absence of a relationship with cortical Aβ may describe a clearance system overwhelmed by Aβ deposition. Absence of group‐wise differences of relative PVS size in WM vessels, along with no vessel‐by‐vessel association of PVS size with nearby GM Aβ suggests that WM PVS size may not be relevant to Aβ clearance at this scale in individuals of advanced age.